End-of-life care for patients with pancreatic cancer in France: a nationwide population-based cohort study - Ugo Marchese; Vanessa Pauly; Anna Pellat; Yasmina Richa; Guillaume Fond; Stylianos Tzedakis; Martin Gaillard; Basile Fuchs; Veronica Orleans; David Fuks; Mehdi El Amrani; Laurent Boyer (Therapeutic Advances in Medical Oncology)
Background: Pancreatic cancer, a frequently fatal disease with severe symptoms, can require high-intensity end-of-life (HI-EOL) care, posing challenges to patients’ well-being. The examination of HI-EOL care to develop tailored interventions in the management of pancreatic cancer is a critical, yet underexplored area. Objectives: The objective of this study was to assess the factors that influence the intensity of end-of-life (EOL) care in France. Design: A retrospective study of patients registered in the French Nationwide database who were hospitalized in France for pancreatic adenocarcinoma from January 1, 2014 to December 31, 2019, and subsequently died during the follow-up period. Methods: Data on patient demographics, clinical characteristics, hospitalization details, and palliative care were collected. The primary outcome measure was the evaluation of HI-EOL care, defined by indicators such as death in an intensive care unit (ICU), multiple hospitalizations, and chemotherapy administration within the last 30 days of life. Secondary outcomes included indicators of most-intensive EOL (MI-EOL) care and invasive procedures (IP). Univariate and multivariate logistic regression analyses were conducted to identify factors associated with each outcome measure. Results: A total of 42,696 patients who died from pancreatic adenocarcinoma were included. Among them, 41.1% experienced HI-EOL, with the most common indicators being multiple hospitalizations and death in an ICU, emergency room, or acute care unit. A smaller proportion (2.8%) received MI-EOL care, while 28.1% underwent IPs in the last 30 days of life. The multivariate analysis revealed that male gender and follow-up in non-cancer specialized care facilities were associated with a higher risk of HI-EOL. Conversely, palliative care involvement and older age at death were identified as protective factors. Male gender, older age at death, and palliative care involvement were associated with lower rates of MI-EOL care and IPs. Conclusion: These results underscore the importance of palliative care integration and individualized approaches in improving the EOL quality of care and patient outcomes for individuals with advanced pancreatic cancer.